Competence-oriented approach tohr management in the restaurant business - V. V. Dzyuba (Вестник Северо-Кавказского федерального университета)
The article discusses the essence and features of the implementation of a competency-based approach to human resource management within the framework of the general management system at the enterprises of the restaurant industry. The main problems of the process of personnel management of public catering organizations in the current conditions of the growth of the digital economy and taking into account current trends in the development of the service sector are highlighted. Grouped directions for the formation of professional knowledge, skills and abilities of restaurant workers and increasing their involvement in labor activity on the following grounds: personnel policy; organizational structure of management; regulatory and legal support of the personnel management system; information support of the personnel management system; employee development; innovations in the work of the staff of the restaurant business; security; corporate culture and ethical standards of behavior of service personnel in public catering facilities. The role of qualified and customer-oriented personnel of the restaurant is substantiated as a way to increase the satisfaction of the guests of the establishment with the level of service and increase the competitiveness of the enterprise in the market. Based on the study of scientific literature and the content of relevant professional standards in the service sector, a competence portrait of the main categories of restaurant employees has been developed, which contributes to better use of personality-oriented tools in the framework of personnel work in the organization and, in general, to increase the efficiency of personnel management in the restaurant business.